Evaluation of Holy Places of the Regions for the Development of Pilgrimage Tourism - Zebiniso Navruz-zoda (Universitas Muhammadiyah Sidoarjo, 2020)
The article is intended to describe the four stages of turning sacred sites into pilgrimage clusters in detail: 1) making sacred sites a place of pilgrimage; 2) promoting sacred places as attractive pilgrimage tourist destinations; 3) forming pilgrimage clusters with high competitiveness on the basis of attractive pilgrimage destinations. In order to form regional pilgrimage tourism clusters it requires to assess the quality and level of accessibility in destinations. For this purpose, the author has established “Criteria for Assessment of Sacred Sites and Procedure for their Qualitative Classification”. It is recommended that the shrines be evaluated on a 100-point scale using the following 10 criteria: a comprehensive range of pilgrimage information; advanced infrastructure of pilgrimages; prestige of pilgrimages; worship of pilgrimages; the rank of sanctity in the shrines; scientific potential of pilgrimages; the type of monuments in the shrine; the historicity of pilgrimages; the prodigy of the pilgrimages; 10) usefulness of the pilgrimages and opportunities to manage them. Based on the results of the multivariate evaluation, it is recommended to distinguish between the three categories of pilgrims: “Sacred Sights”, “Pilgrimage Place” and “Attractive Sanctuary”. Estimating the quality of pilgrimages in Bukhara region with the mentioned established method. This article demonstrates comparative analysis and recommendations for the selection of facilities for the “Seven Saints” pilgrimage cluster.